2020
DOI: 10.11646/zootaxa.4808.2.6
|View full text |Cite
|
Sign up to set email alerts
|

Paragoniosomatinae, a new subfamily of Gonyleptidae (Arachnida: Opiliones), based on a new species from the Chapada Diamantina relict cloud forests, Brazil

Abstract: In this paper, we describe a new subfamily of Gonyleptidae, Paragoniosomatinae subfam. nov., based on a new genus and species, Paragoniosoma cachaceiro gen. nov., sp. nov., found in an upper montane cloud forest of Chapada Diamantina mountains, one of the small interior patches of Atlantic Forest. This discovery suggests that the narrow-restricted cloud forests are old relicts of an Atlantic Forest hotspot. Paragoniosoma cachaceiro gen. nov., sp. nov. is characterized by the presence of four areas on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 835 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…After the original proposal, the AE11 pattern has been routinely applied by different research groups to species descriptions in the families Cosmetidae (e.g., Damron et al 2018;Friedrich & Lehmann 2020), Epedanidae (e.g., Zhang & Martens 2018), Gonyleptidae (e.g., Hara et al 2018;Acosta 2020;Araujo-da-Silva et al 2020) and Stygnopsidae (e.g., Cruz-López & Francke 2016, 2019, 2020. Kury & Villarreal (2015) suggested that the AE11 pattern may also occur in other superfamilies of Laniatores, such as Assamioidea and Epedanoidea (sensu Ferna´ndez et al 2017), but the authors did not further pursue this matter.…”
mentioning
confidence: 99%
“…After the original proposal, the AE11 pattern has been routinely applied by different research groups to species descriptions in the families Cosmetidae (e.g., Damron et al 2018;Friedrich & Lehmann 2020), Epedanidae (e.g., Zhang & Martens 2018), Gonyleptidae (e.g., Hara et al 2018;Acosta 2020;Araujo-da-Silva et al 2020) and Stygnopsidae (e.g., Cruz-López & Francke 2016, 2019, 2020. Kury & Villarreal (2015) suggested that the AE11 pattern may also occur in other superfamilies of Laniatores, such as Assamioidea and Epedanoidea (sensu Ferna´ndez et al 2017), but the authors did not further pursue this matter.…”
mentioning
confidence: 99%